PROFITABILITY, LEVERAGE, SIZE OF COMPANY TOWARDS TAX AVOIDANCE - Kimsen, Kimsen; Kismanah, Imas; Masitoh, Siti (Universitas Pakuan, 2018)
The purpose of this research is to know the influence of Return On Assets (ROA), Debt ToEquity Ratio (DER), and Asset to Tax Avoidance (TA) partially and Together in the Sector of AnekaIndustri company listed in Indonesia Stock Exchange (IDX). The research period used is 5 years theperiod 2012-2016. The study population included all industry miscellaneous sectors listed inIndonesia Stock Exchange (IDX) period 2012-2016. Sampling technique used purposive samplingtechnique. Based on the predetermined criteria, the sample size was 8 companies. The type ofdata used was secondary data obtained from the Indonesia Stock Exchange website. Data analysismethod used was panel data regression analysis. The result of Uji F explained that the model inthis research was feasible so that the test was continued with the t-test and the significance test,which showed that the Return On Assets had an effect on Tax Avoidance, Debt to Equity Ratio had a positive influence on Tax Avoidance, Ln Assets Negative to Tax Avoidance.Keywords: Tax Avoidance, Return On Assets, Debt To Equity Ratio, Asset.